2006
DOI: 10.1177/1534735406291962
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Strength, Body Composition, and Physical Activity in Women Receiving Chemotherapy for Breast Cancer

Abstract: There is evidence to suggest that treatment of breast cancer with chemotherapy can induce metabolic changes in skeletal muscle. Women undergoing treatment for breast cancer with certain chemotherapeutic agents can experience declines in lean body mass and muscle strength and a subsequent increase in body weight. These alterations not only can lead to declines in physical function but also predispose women to weight-related chronic illness. Excess body weight may also play a role in the development or recurrenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
52
0
9

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(63 citation statements)
references
References 48 publications
2
52
0
9
Order By: Relevance
“…Surgery, chemotherapy, and radiation therapy are known to decrease exercise capacity, muscle strength and QoL in lung cancer patients [15,17,20,27,28,35,36]. The results of the present study are in line with previously reported data.…”
Section: Discussionsupporting
confidence: 83%
“…Surgery, chemotherapy, and radiation therapy are known to decrease exercise capacity, muscle strength and QoL in lung cancer patients [15,17,20,27,28,35,36]. The results of the present study are in line with previously reported data.…”
Section: Discussionsupporting
confidence: 83%
“…El ejercicio físico es considerado una intervención no farmacológica eficaz en la promoción del bienestar físico, mental y funcional de pacientes con cáncer 10,11,12 . Cramp & Byron 13 en una revisión sistemática encontraron que el ejercicio físico produjo mejoras significativas en la fatiga de pacientes con cáncer durante y después del tratamiento activo; aunque los autores no realizaron estimaciones del efecto de las modalidades de ejercicio estudiadas.…”
Section: Introductionunclassified
“…Studies have also shown promising effects of physical activity on fatigue, physical function, physical capacity and muscular fitness during, and after cancer treatment [5,[10][11][12][13]. In particular, breast cancer patients who exercise have reported decreased levels of anxiety and depression, coupled with overall mood elevation [3].…”
Section: Introductionmentioning
confidence: 99%